2015
DOI: 10.1016/j.lwt.2014.10.050
|View full text |Cite
|
Sign up to set email alerts
|

Exquisite wild mushrooms as a source of dietary fiber: Analysis in electron-beam irradiated samples

Abstract: In the present study, electron-beam irradiation was applied to dried samples of Boletus edulis and Macrolepiota procera to evaluate the effects on their fiber composition. Both species presented an important percentage of dietary fiber, soluble and insoluble in different ratios. These high fiber levels are an interesting feature, allowing considering mushrooms as an alternative source of dietary fibers in the highly competitive market of fiber-enriched food products. In B. edulis samples, insoluble fiber and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…T. melanosporum proteins are rich in sulphur amino acids (Harki et al, 2006) forming disulphide bonds to maintain their ternary structure and they are particularly sensitive to the free radicals generated after irradiation (Ibarz, 2008). Similar results were also noticed when mushrooms (Boletus edulis and Russula delica) were submitted to electron-beam irradiation (Fernandes et al, 2014).…”
Section: Effect Of Irradiation Treatmentssupporting
confidence: 79%
“…T. melanosporum proteins are rich in sulphur amino acids (Harki et al, 2006) forming disulphide bonds to maintain their ternary structure and they are particularly sensitive to the free radicals generated after irradiation (Ibarz, 2008). Similar results were also noticed when mushrooms (Boletus edulis and Russula delica) were submitted to electron-beam irradiation (Fernandes et al, 2014).…”
Section: Effect Of Irradiation Treatmentssupporting
confidence: 79%
“…Mushrooms’ cell wall components contain non-digestible carbohydrate and fiber that can be adequately utilized to augment the nutritional content of some low fibre foods. The findings of Cheung ( 16 ) and Fernandes et al ( 18 ) reported the health benefits of dietary fibre, which include the following: constipation relief, prevention of colon disease, and hemorrhoids as well as maximizing the viscosity of the food matrix, slowdown of digestion, lower blood glucose, and strengthens immune system with antitumor activity. Hence, mushrooms are excellent source of dietary fiber that can be used for the enrichment of biopharmaceutical products.…”
Section: Discussionmentioning
confidence: 99%
“…The structure of certain types of mushroom provide a mouthfeel and umami flavor which resembles that of meat, often perceived as a vegan alternative (Jo-Feeney et al, 2014). Moreover, the cell wall components of mushroom contain chitin, 1-3-alpha-D-gucans and mannans, which confer nutritional benefits, such as dietary fiber (Cheung, 2013;Fernandes et al, 2015). The antimicrobial and nutritional properties, alongside its animal-free nature and abundancy, make chitin/chitosan-based scaffolds a potential substrate for cellular agriculture applications.…”
Section: Chitin and Chitosanmentioning
confidence: 99%